(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyses preventive measures during proceedings of land market in the countries of Europe, Argentine and the existing state of land relations in Ukraine. The problem of land market regulation belongs to the most important spheres of state economic policy. Ukraine is close to cancel the moratorium on lands of agricultural usage, that is why it is not surprisingly that big agrarian companies increase intensively their land assets. The foundations of state regulation of market land relations as the form of limitation by the state the freedom of entrepreneurship aiming at achievement of socially meaningful goals are justified. So this process demands the detailed research and analysis with the purpose of working out recommendations as to efficiency boom of agrobusiness and prevention of negative phenomena and tendencies. The author proposes the necessity of urgent steps before the opening of land market and to reflect preventive measures in the law «On selling lands of agricultural purpose»: – citizens of Ukraine can buy lands of agricultural purpose and who will personally conduct economic activity, live on lands location, have adequate qualification or experience of conducting agricultural production and use land according to purpose destination and not to sublease it; – the first priority of buying lands have co-owners, tenants, owners of neighboring plots, citizens residing in given location and have adequate education, or working experience in agriculture, local authorities or executive bodies; – maximum land ownership and land use must be determined by the law «On selling lands of agricultural purpose» depending on nature and climate zones where lands of agricultural purpose are located; – these legal positions do not concern lands which are provided for conducting personal agricultural farming, gardening. These measures will promote successful development of agricultural sector on the basis of national small and medium business based on organic agriculture and will allow to revive Ukrainian agriculture, to create proper social conditions of living in rural area and to make Ukraine a rich country.